Renal function is associated with 1-month and 1-year mortality in patients with ischemic stroke. (February 2018) - ,; Liu, Chung-Hsiang; Tsai, Chon-Haw; Huang, Wei-Shih; Lu, Chung-Ta; Tsai, Tzung-Chang; Tseng, Chun-Hung; Lin, Kang-Hsu; Shyu, Woei-Cherng; Yang, Yu-Wan; Liu, Yen-Liang; Cho, Der-Yang; et al.
Abstract: Background and aims: Renal dysfunction is a potent risk factor for cardiovascular diseases, including stroke. This study aimed to evaluate the impact of admission estimated glomerular filtration rate (eGFR) levels on short-term (1-month) and long-term (1-year) mortality in patients with acute ischemic stroke. Methods: From the Taiwan Stroke Registry data, we classified ischemic stroke patients, identified from April 2006 to December 2015, into 5 groups by eGFR at admission: ≥ 90, 60–89, 30–59, 15–29, and <15 mL/min/1.73 m 2 or on dialysis. Risks of 1-month mortality and 1-year mortality after ischemic stroke were investigated by the eGFR level. Results: Among 52, 732 ischemic stroke patients, 1480 died within one month. The 1-month mortality rate was over 5-fold greater in patients with eGFR <15 mL/min/1.73 m 2 or dialysis than in patients with eGFR ≥90 mL/min/1.73 m 2 (2.88 versus 0.56 per 1000 person-days). The adjusted hazard ratio (HR) of 1-month mortality increased from 1.31 (95% CI = 1.08–1.59) for patients with eGFR 60–89 mL/min/1.73 m 2 to 2.33 (95% CI = 1.80–3.02) for patients with eGFR < 15 mL/min/1.73 m 2 or on dialysis. 3226 patients died within one year. The adjusted HR of mortality increased from 1.38 (95% CI = 1.21–1.59) for patients with eGFR 60–89 mL/min/1.73 m 2 to 2.60 (95% CI 2.18–3.10) for patients with eGFR < 15 mL/min/1.73 m 2 or on dialysis, compared to patients with eGFR ≥ 90 mL/min/1.73 m 2 . Conclusions: After acute ischemic stroke, patients with reduced eGFR are at elevated risks of short-term and long-term deaths in a graded relationship. Highlights: This study aims to evaluate the short-term (1-month) and long-term (1-year) mortality for patients with acute ischemic stroke by the glomerular filtration rate (eGFR) levels measured at admission: ≥ 90, 60–89, 30–59, 15–29, and <15 mL/min/1.73 m 2 or on dialysis. Patients with reduced eGFR were at higher risk of dying either at short- or long-term in a graded relationship.